2013
DOI: 10.1088/2040-8978/15/11/114006
|View full text |Cite
|
Sign up to set email alerts
|

Soft-boundary graphene nanoribbon formed by a graphene sheet above a perturbed ground plane: conductivity profile and SPP modal current distribution

Abstract: An infinite sheet of graphene lying above a perturbed ground plane is studied. The perturbation is a two dimensional ridge, and a bias voltage is applied between the graphene and the ground plane, resulting in a graphene nanoribbonlike structure with a soft-boundary (SB) The spatial distribution of the graphene conductivity forming the soft-boundary is studied as a function of the ridge parameters and the bias voltage. The current distribution of the fundamental TM surface plasmon polariton (SPP) is considered… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
(42 reference statements)
0
16
0
1
Order By: Relevance
“…It is also important to mention that the fringing electrostatic fields between consecutive polysilicon pads can be neglected and, therefore, they do not perturb the conductivity profile along the z-axis on graphene. First, it is shown in [36] that a finite-width gating pad imposes a soft boundary condition on the graphene sheet, leading to a smooth conductivity profile. Second, in order to provide a sinusoidal modulation of graphene's surface reactance, consecutive pads are DC biased with relatively similar voltages (as graphically illustrated in Fig.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…It is also important to mention that the fringing electrostatic fields between consecutive polysilicon pads can be neglected and, therefore, they do not perturb the conductivity profile along the z-axis on graphene. First, it is shown in [36] that a finite-width gating pad imposes a soft boundary condition on the graphene sheet, leading to a smooth conductivity profile. Second, in order to provide a sinusoidal modulation of graphene's surface reactance, consecutive pads are DC biased with relatively similar voltages (as graphically illustrated in Fig.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…For simplicity, here we have considered an ideal modulation and thin gating pads with highly resistive THz response (such as polysilicon or ITO), allowing us to neglect their influence in the EM analysis. This is a welljustified approximation based on previous comprehensive studies on gated graphene plasmonics biased with static voltages [7][6], [17]. Moreover, practical designs may further reduce the influence of the bias circuitry by using self-biased graphene layers [19] or metasurfaces designed to be transparent at the frequency of operation.…”
Section: Graphene Plasmonic Isolatormentioning
confidence: 97%
“…1 have already been applied to develop filters [7] and leaky-wave antennas [6] based on a static spatial modulation of graphene conductivity. In addition, recent studies have confirmed that the carriers injected by the biasing gates lead to a smooth modulation of graphene conductivity along the sheet, the so-called 'soft boundary conditions' [17]. In the following, we add a temporal dependence to this picture by adequately biasing all gating pads to achieve a conductivity modulation profile in the bottom graphene layer that has the form of a monochromatic travelling perturbation (see Fig.…”
Section: Spatiotemporal Modulation Of Graphenementioning
confidence: 99%
“…In order to realize on-chip graphene plasmonics, the fundamental is to make an excellent waveguide. People have proposed several types of graphene plasmonic waveguides (GPWGs) 9 18 21 22 23 24 25 26 27 28 and most of them are made with graphene ribbons 18 21 22 25 26 . However, the edge scattering effect and band gap opening in a graphene ribbon introduce extra plasmon damping to GSPs 18 29 .…”
mentioning
confidence: 99%
“…However, the electrical operation for the gating pads is complicated due to more than one pads involved, particularly when two or more waveguides are placed close to each other (which is necessary for lots of photonic integrated devices). A patterned spacer layer can also be utilized by introducing a nano-ridge structure 9 23 24 or more than one materials 9 such that only one gate voltage is needed. One should note that the fabrication for the spacer with different materials is not convenient.…”
mentioning
confidence: 99%